Onset of breast and pubic hair development in 1231 preadolescent Lithuanian schoolgirls. Issue 9 (26th April 2005) - Žukauskaitė, S; Lašienė, D; Lašas, L; Urbonaitė, B; Hindmarsh, P
Abstract : Background: Correct staging of puberty is essential in order to differentiate different pathologies, as various components of the endocrine system influence breast, pubic, and axillary hair development. Aims: To determine the current timing of adrenarche and breast development in Lithuanian preadolescent schoolgirls. Methods: Cross-sectional study of 1231 schoolgirls aged 7.0–11.6 years. Puberty was staged according to the method of Tanner. Mean age at entry into each pubertal stage was calculated by probit analysis. Results: Of the 255 girls aged 7 years, two had premature adrenarche (0.8%) and one premature thelarche (0.4%). Mean age of onset of pubic/axillary hair development was 11.0 years, and for breast development (Stage 2) 10.2 years. Breast Stage 3 development was attained at 11.3 years and Stage 4 at 13.9 years. Mean BMI, height, weight, and systolic blood pressure SD scores were higher in pubertal than in prepubertal girls. Skinfold thickness was also significantly higher in girls with isolated adrenarche than in prepubertal girls. The increase in BMI and weight resulted from an increase in body fat as evidenced by measures of subscapular and triceps skinfold thickness. Girls with only signs of adrenarche or thelarche did not differ from each other from the anthropometric standpoint. Conclusions: Premature thelarche and premature adrenarche were relatively uncommon in this population. Pubertal onset was slightly earlier than the UK Tanner standards and tended to occur in girls with a higher BMI.